The G.P.I. and the speech pathologist - Shetty, Prathibha S (Journal of All India Institute of Speech and Hearing, 1970)
’Half a century ago general paralysis of the insane constituted a high pro- portion of mental hospital admissions and accounted for an appreciable part of the chronic population of such institutions. However, with the development of increasingly effective methods of treatment, cerebral syphillitic infection is becoming relatively rare’ (Mayer-Gross et al., 1960)